Clinical and radiological outcomes of surgically treated osteochondral lesions of the talus in children and adolescents. (June 2023) - Kim, Dae-Yoo; Park, JiSu; Kang, Ho Won; Shin, Chang Ho; Lee, Dong Yeon; Cho, Tae-Joon; Yoo, Won Joon
Background: Osteochondral lesions of the talus are uncommon in children and adolescents. Surgical procedures differ from those used for adults to avoid iatrogenic physeal injuries. This study aimed to evaluate the clinical and radiological outcomes of surgical treatment in pediatric patients with osteochondral lesions, specifically investigating the patient age and the status of distal tibial physis as factors associated with surgical success. Methods: We retrospectively reviewed 28 patients who had symptomatic osteochondral lesions of the talus that were treated surgically between 2003 and 2016. If the lesion was stable and articular cartilage was intact, retrograde drilling was performed under fluoroscopic guidance. Lesions with detached overlying cartilages were treated by debridement of the cartilage combined with microfracture and drilling. Radiographic outcomes, American Orthopaedic Foot & Ankle Society ankle-hindfoot score, and skeletal maturity were evaluated. Results: Radiological improvement was observed in 24 (24/28, 86%) patients and complete and incomplete healing in 8 and 16 patients, respectively. Changes in pain grades, American Orthopaedic Foot & Ankle Society scores, and radiological healing after surgery were significant (pain grade, p < 0.001; American Orthopaedic Foot & Ankle Society, p = 0.018; radiological healing, p < 0.001). In addition, patients in the younger age group (≤13 years) showed greater improvements in pain grades than older patients (p = 0.02). Improvement in pain grade after surgery was better in the skeletally immature group than in the skeletally mature group (p = 0.048). Conclusion: Clinical and radiological improvements were observed after surgical treatment. The younger age group and open physis group showed more pain improvement. Level of evidence: Therapeutic level IV.